Clinical results of stereotactic body radiotherapy (SBRT) in the treatment of isolated local recurrence of pancreatic cancer after R0 surgery: A retrospective study. Issue 4 (April 2017) - Comito, T.; Cozzi, L.; Zerbi, A.; Franzese, C.; Clerici, E.; Tozzi, A.; Iftode, C.; Navarria, P.; D'Agostino, G.; Fogliata, A.; Mancosu, P.; Tomatis, S.; et al.
Abstract: Objective: To evaluate the efficacy and the feasibility of SBRT for selected patients with isolated local recurrence of pancreatic cancer after radical surgery. Methods: A retrospective analysis was performed on patients treated with SBRT for isolated local recurrence from resected pancreatic adenocarcinoma, after multidisciplinary board evaluation. Prescription dose was 45 Gy in 6 fractions for all patients. Primary end-point was freedom from local progression (FFLP). Secondary end-points were overall survival (OS), progression free survival (PFS) and toxicity. Local control was defined according to RECIST criteria. Acute and late toxicity was scored according to the NCI Common Terminology Criteria for Adverse Events (CTCAE) v4.0. Results: Between January 2011 and February 2015, 31 patients with isolated local recurrence of resected pancreatic cancer were treated with SBRT. Pancreato-duodenectomy (PD) was performed on 24 patients and distal pancreatectomy (DP) in 7 cases, all with radical resection (R0). Median local recurrence disease free interval (DFI) was 14 months. Median follow-up was 12 months. FFLP was 91% and 82% at 1 and 2-years, respectively. Median PFS was 9 months. Median OS was 18 months. At univariate analysis, OS was correlated with a DFI > 18 months. No cases of acute G3 toxicity or greater occurred. Conclusions: SBRT seems to be an effective and safe therapeutic option for isolated local recurrence of pancreatic cancer after surgery. Encouraging local control rate, very low toxicity profile and effective pain control suggest the crucial role of SBRT in the treatment of these long-survivors selected patients.